Increased levels of HMGB1 and pro-inflammatory cytokines in children with febrile seizures - Choi, Jieun (BioMed Central, 2011)
OBJECTIVE: Febrile seizures are the most common form of childhood seizures. Fever is induced by pro-inflammatory cytokines during infection, and pro-inflammatory cytokines may trigger the development of febrile seizures. In order to determine whether active inflammation, including high mobility group box-1 (HMGB1) and pro-inflammatory cytokines, occurs in children with febrile seizures or epilepsy, we analyzed cytokine profiles of patients with febrile seizures or epilepsy. METHODS: Forty-one febrile seizure patients who visited the emergency department of Seoul National University Boramae Hospital from June 2008 to May 2009 were included in this study. Blood was obtained from the febrile seizure child patients within 30 minutes of the time of the seizure; subsequently, serum cytokine assays were performed. Control samples were collected from children with febrile illness without convulsion (N = 41) and similarly analyzed. Serum samples from afebrile status epilepticus attacks in intractable epilepsy children (N = 12), afebrile seizure attacks in generalized epilepsy with febrile seizure plus (GEFSP) children (N = 6), and afebrile non-epileptic controls (N = 7) were also analyzed. RESULTS: Serum HMGB1 and IL-1β levels were significantly higher in febrile seizure patients than in fever only controls (p < 0.05). Serum IL-6 levels were significantly higher in typical febrile seizures than in fever only controls (p < 0.05). Serum IL-1β levels were significantly higher in status epilepticus attacks in intractable epilepsy patients than in fever only controls (p < 0.05). Serum levels of IL-1β were significantly correlated with levels of HMGB1, IL-6, and TNF-α (p < 0.05). CONCLUSIONS: HMGB1 and pro-inflammatory cytokines were significantly higher in febrile seizure children. Although it is not possible to infer causality from descriptive human studies, our data suggest that HMGB1 and the cytokine network may contribute to the generation of febrile seizures in children. There may be a potential role for anti-inflammatory therapy targeting cytokines and HMGB1 in preventing or limiting febrile seizures or subsequent epileptogenesis in the vulnerable, developing nervous system of children.